EVALUASI TINGKAT KESELAMATAN PERKERETAAPIAN DI INDONESIA (Sekretariat Badan Kebijakan Transportasi, Formerly by Puslitbang Transportasi Laut, Sungai, Danau, dan Penyeberangan, 2014)
ABSTRACTThe decrasing of train accident can be solve with the quality safety system, in this case is safety guarantee for Railway Transportation. The purpose of this study is to evaluate the safety level of the railroad in Indonesia which is to minimize the accident rate by approacing Human Factors Analysis and Clasification System (HFACS), which the human factor and other factors has contribut to the accident. Through this approaches can be grouping by indicators train wreck through hierechy taxonomic classification, namely Human Factors Analysis and Clasification System-Rail Road (HFACS-RR), consisting of Outside Factors, Organizational Factors, Supervisory Factors, Preconditions for Operator Acts, and Acts Operator. HFACS-RR approach can be seen as the cause of train accidents which can be caused by outsider influences 11 occurenciess, 10 occurenciess organizational influences, unsafe supervision, 12 occurenciess, precondition for unsafe act 9 occurenciess, and unsafe acts 2 occurenciess. Refers to the details of the Plan of Action Enhancement of Railway Transportation Safety field theory HFACS-RR can be grouping with some action plan,consist ot HW (Hardware) 22 items, SW (Software) 10 items, BW (Human Resources) 8 items, MI (Setup Board) 4 items.ABSTRAKPenurunan resiko kecelakaan kereta api dapat dilakukan melalui penerapan sistem jaminan kualitas, dalam hal ini adalah jaminan keselamatan dalam bidang transportasi kereta api. Tujuan dari Penelitian ini adalah mengevaluasi tingkat keselamatan perkeretaapian di Indonesia untuk meminimalkan tingkat kecelakaan dengan pendekatan Human Factors Analysis and Clasification System (HFACS), dimana faktor manusia dengan faktor lainnya memiliki kontribusi terhadap terjadinya kecelakaan. Melalui pendekatan tersebut dapat dikelompokkan penyebab kecelakaan kereta api melalui klasifikasi taksonomi hierarkis, yaitu Human Factors Analysis and Clasification System-Rail Road (HFACS-RR), terdiri dari Outside Factors, Organizational Factors, Supervisory Factors, Preconditions for Operator Acts, dan Operator Acts. Melalui pendekatan HFACS-RR dapat diketahui bahwa penyebab kecelakaan kereta api dapat disebabkan outside influences 11 kejadian, organizational influences 10 kejadian, unsafe supervision 12 kejadian, precondition for unsafe act 9 kejadian, dan unsafe acts 2 kejadian. Mengacu pada butir-butir Rencana Aksi Peningkatan Keselamatan Transportasi bidang Perkeretaapian dengan teori HFACS-RR dapat dikelompokkan beberapa butir rencana aksi yaitu HW (Perangkat Keras) 22 butir, SW (Perangkat Lunak) 10 butir, BW (Sumber Daya Manusia) 8 butir, MI (Penataan Lembaga) 4 butir.